Oil Price Shocks Dynamics, Stock Market Dynamics, and Exchange Rate Dynamics - Yeni Suseni; Bintang Rizky; Putri Ayu; Weriantoni Weriantoni (Universitas Gorontalo, 2023)
This research was conducted to determine the influence of oil price, stocks and exchange rates in Indonesia. The data used in this research is secondary data in the form of time series data stretching from November 2014 to November 2022. The Quantitative research method, which is VAR (Vector Autoregressive) was used to test and analyze hypotheses with measurable data to obtain parameters from the variables’ influence. The study’s results found that oil prices significantly influenced Indonesia’s stock prices decline. Oil on the exchange rate was also significant, meaning last month's oil prices affected the exchange rate this month, and there was a depreciation. Still, the exchange rate was not significant for stock prices.